TRI HITA KARANA SEBAGAI LANDASAN FILSAFAT KOMUNIKASI DALAM PENGEMBANGAN DESA WISATA: PERSPEKTIF TEORI INTERAKSI SIMBOLIK - Juliani, Komang; Suciani, Ni Nyoman; Andini, Desak Putu Adistya; Widaswara, Rieka Yulita (IAHN Gde Pudja Mataram, 2024)
Tri Hita Karana is a Hindu communication philosophy which consists of human relationships with God (Parahyangan), relationships between humans (Pawongan), and human relationships with nature (Palemahan). Tri Hita Karana is implemented by Buwun Sejati Hindus in developing their village as a tourist village. This research is located in the tourist village of Buwun Sejati. The research focus is on the implementation of Tri Hita Karana as a communication philosophy, and its relationship with symbolic interaction theory. The research method is a qualitative descriptive method, where the research findings will be narrated in words. The results of the research show that the implementation of Tri Hita Karana carried out by Buwun Sejati Hindus includes the implementation of the Parahyangan concept in the communal prayer ritual to commemorate the holy Nyepi holiday. The implementation of a life full of tolerance carried out by Hindus as the implementation of pawongan is by maintaining security carried out by pecalang during the Friday prayers of Muslims. The concept of weakening was implemented by the Buwun Sejati Hindu community who were also members of the Hindu religious instructors in tree planting movement activities in the West Lombok area, one of which was in Buwun Sejati Village. The relationship between the Tri Hita Karana concept and the theory of symbolic interaction in the development of the Buwun Sejati natural tourism village includes symbols in culture, meaning in social relations, the process of negotiating meaning, respect for nature, and finally cultural identity.